The Voices of Baseball: The Game's Greatest Broadcasters Reflect on America's Pastime - McKnight, Kirk (Rowman & Littlefield Publishers, 2023)
A fascinating tour of baseball’s greatest moments and iconic stadiums, told through the reminiscences of 50 play-by-play broadcasters. With careers spanning two to three times that of an average player, baseball’s best broadcasters have no shortage of history to offer. They have witnessed opening days, no hitters, slugfests, and perfect games, all from arguably the best seats in the house. Broadcasters know their clubs, their stadiums, and their teams in a way that no one else can. In The Voices of Baseball: The Game's Greatest Broadcasters Reflect on America's Pastime, Updated Edition, Kirk McKnight provides an in-depth look at each of Major League Baseball’s thirty ballparks from the perspectives of the game’s longest-tenured storytellers. Fifty broadcasters reflect on their most iconic calls, fondest memories, what makes their ballparks unique, and more. This updated edition includes 14 additional broadcasters, two new stadiums, the latest World Series calls from the booth, and a special tribute to the recently-departed Vin Scully. With decades of broadcasting between them, their stories encapsulate some of Major League Baseball’s biggest moments. Generations of baseball fans will all enjoy the historic and triumphant memories shared by some of the game’s greatest broadcasters in The Voices of Baseball.